PENGARUH PERMAINAN TRADISIONAL GELENG TERHADAP KEMAMPUAN EMOSIONAL ANAK USIA 5-6 TAHUN DI TK PERTIWI SELONG - zuhud ramdhani; najamuddin najamuddin; rohyana fitriani (Universitas Hamzanwadi, 2023)
The study aimed at knowing the effect of the traditional rocking game on the emotional ability aged 5-6 years old at Pertiwi Selong kindergarten, academic year 2020/2021. This study used a quantitative research by using experimental method with a one group pretest-posttest desigen. Research subjects were determined by the saturated sample technique with a total of 19 children in group B4. Data collection techniques were carried out trought observation, documentation and t-test. The results of the study showed that there was an effect of the traditional game of shaking hands on children’s emotional abilities t -count > t-table (21,35416 > 1,73406) so that the hypothesis was accepted. The difference in the emotional ability of children with the pretest obtained an average total percentage of 36% achieved by all children and is included in the percentage of the assessment category “ Starting to Develop (SD)” and after being given treatment and posttest the total average percentage increases from the previous 78% with the category “ Very Well Develop (VWD)”.